SEM-PLS DALAM MENGANALISIS PERSEPSI DAN PREFERENSI MASYARAKAT KECAMATAN DANAU KERINCI TERHADAP WISATA EKOLOGI (ECOTOURISM) - Reza, Aidini Desfa; Sufri, Sufri; Mardhotillah, Bunga (Inovasi Pembangunan : Jurnal Kelitbangan, 2024)
This study aims to determine the SEM-PLS model of the perception and preferences of the Danau Kerinci District community towards the Danau Kerinci Ecotourism Area, Pertiwi Pentagen Park, Sanggaran Agung Pine Forest, Pasir Panjang Beach, Tanjung Tanah Village and Talang Kemulun Waterfall. This research method uses a Mixed Research approach, which is descriptive and inferential. Qualitative and quantitative descriptive analysis is applied in SEM-PLS modeling using SmartPLS software by measuring, analyzing, and interpreting the perception and preferences of the community towards ecological tourism in Danau Kerinci District. The type of data used in this study is primary data obtained directly through distributing questionnaires to residents. The data consists of 8 variables, namely 4 exogenous variables, 3 moderating variables and 1 endogenous variable. The results of the study based on the analysis using SmartPLS software shows that all exogenous variables have a significant effect on public perception and preferences. Cleanliness of facilities, accessibility, attractiveness, and infrastructure conditions increase positive perceptions, while the uniqueness of tourist attractions and the potential for improving welfare also strengthen public interest. Model evaluation shows high validity and reliability, with strong R-square and Q-Square Predictive Relevance values. The conclusion of this study is that public perception and preferences for ecotourism in Danau Kerinci District are influenced by various factors that can be used as a basis for developing strategies to improve the quality of ecotourism in the area.